The effect of financial skills and strategies toward saving behavior among self-employed workers in retirement planning - Nazimuddin, Wan Anura Wan; Foziah, Nik Hazimi Mohammed; Afthanorhan, Asyraf (Asian Development Policy Review, 2024)
This paper aimed to investigate essential factors of financial skills and financial strategies that influence retirement savings behavior among self-employed workers. Many retirement savings schemes are being introduced by regulatory bodies or financial institutions, especially for self-employed workers on a voluntary basis, but many people's efforts to save for retirement are stalled. However, the participation of self-employed workers in those schemes is still low as people have financial instability or lack of knowledge in matters. The quantitative approach is applied by distributing a systematic random sampling of 400 prospective respondents. The outcome was analyzed using Structural Equation Modelling (SEM) indicates that savings behavior financial skill, financial strategies, and demographics positively moderated relationship. This study adds to the existing knowledge on financial skills as well as financial strategies towards saving objectives for self-employed, with practical implications for promoting positive saving habits and improving financial well-being across all age groups. Policymakers might use the data to create targeted programs that specifically target self-employed workers and promote responsible saving and financial security across generations. The authorities should construct a comprehensive fixed retirement scheme for self-employed workers based on these characteristics so that self-employed workers have secure and stable financial security after retirement.